Monday
March 27, 2017

Post a New Question

Posted by on .

How do I solve 3log10of(x-6)=11 and e^(2x)+10e^(x)-25=0?

  • Math - ,

    3log10of(x-6)=11
    log 10 (x-6)^3 = 11
    (x-6)^3 = 10^11
    x-6 = 10^(11/3)
    x = 10^(11/3) + 6

    for the second, let e^x = a
    then we have
    a^2 + 10a - 25 = 0
    (a-5)^2 = 0
    a = +- 5
    e^x = 5 or e^x = -5 (the second has no solution)
    x = ln5

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question